Research priorities to strengthen environmental cleaning in healthcare facilities: the CLEAN Group Consensus - Giorgia Gon; Angela Dramowski; Emilio Hornsey; Wendy Graham; Nasser Fardousi; Alexander Aiken; Benedetta Allegranzi; Darcy Anderson; James Bartram; Sanjay Bhattacharya; John Brogan; An Caluwaerts; et al. (Antimicrobial Resistance and Infection Control, 2024)
Abstract Environmental cleaning is essential to patient and health worker safety, yet it is a substantially neglected area in terms of knowledge, practice, and capacity-building, especially in resource-limited settings. Public health advocacy, research and investment are urgently needed to develop and implement cost-effective interventions to improve environmental cleanliness and, thus, overall healthcare quality and safety. We outline here the CLEAN Group Consensus exercise yielding twelve urgent research questions, grouped into four thematic areas: standards, system strengthening, behaviour change, and innovation.